ANALISIS PENGARUH PERPUTARAN KAS, PERPUTARAN PERSEDIAAN, PERPUTARAN PIUTANG TERHADAP TINGKAT LABA SERTA DAMPAKNYA TERHADAP HARGA SAHAM (Studi Terhadap Perusahaan Otomotif pada Malaysia Exchange Stock Tahun 2011-2016) - Saksono Budi (Universitas Pamulang, 2019)
AbstractThis study aims to analyze the effect of cash turnover, inventory turnover, receivable turnover to profit rate and its impact on stock prices at automotive companies listed on the Malaysia Stock Exchange. The population in this study finished 10 registered compananies on the Malaysian ExchangeStock period 2011-2016. In this research obtained finished 5 (five) companies determined as sample, companies that were used as samples taken using purposive sampling method,. Statistical testimg is done using regression test of panel data of random effect Eviews 9.0 model. this research method uses descriptivequantitative by doing the activity of collecting secondary data from company annual report. Cash turnover, inventory turnover, receivable turnover as independent variable, and net profit as moderating variable. While stock price is measured by Change of stock price. The results showed that simultaneously, variable cash turnover, inventory turnover and receivable turnover significantly affect the level of earnings. Partially, inventory turnover and receivable turnover have a positive and significant influence to profit rate but cash turnover variable has negative and significant influence to profit rate. While the level of profit has a positive and significant effect on stock prices.